Mathematical methods for curves and surfaces : 9th International Conference, MMCS 2016, Tønsberg, Norway, June 23-28, 2016, Revised selected papers /: 9th International Conference, MMCS 2016, Tønsberg, Norway, June 23-28, 2016, Revised selected papers. (2017) - Unknown
No abstract available